2015
DOI: 10.18677/enciclopedia_biosfera_2015_228
|View full text |Cite
|
Sign up to set email alerts
|

SUPERAÇÃO DE DORMÊNCIA EM SEMENTES DE Tachigali myrmecophila (Ducke) Ducke

Abstract: RESUMOObjetivou-se avaliar diferentes métodos de superação de dormência de sementes para potencializar a propagação de Tachigali myrmecophila (Ducke) Ducke. Foram realizados cinco tratamentos: testemunha -fazendo-se apenas a assepsia das sementes por meio da imersão em hipoclorito de sódio (2%) por cinco minutos; escarificação mecânica -assepsia das sementes por meio da imersão em hipoclorito de sódio (2 %) por cinco minutos e abrasão da superfície da semente à lixa nº 80, no lado oposto à micrópila das sement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…On the other hand, the seeds that received the treatment in hot water at 80°C and those that did not receive pre-germination (control) presented a low percentage of germination, with 42.4% and 7.2%, respectively (Table 1). Similar results were obtained in a study carried out by Pereira et al (2015), in which the seeds of Tachigali myrmecophila submitted to sulfuric acid at 20 minutes and mechanical scarification, obtained the best results to break dormancy, with percentages of germination above 80%. Pilon et al (2012) obtained satisfactory results with scaling in sandpaper and sulfuric acid to overcome dormancy in Tachigali vulgaris seeds, with germination percentages of 84% and 71%, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, the seeds that received the treatment in hot water at 80°C and those that did not receive pre-germination (control) presented a low percentage of germination, with 42.4% and 7.2%, respectively (Table 1). Similar results were obtained in a study carried out by Pereira et al (2015), in which the seeds of Tachigali myrmecophila submitted to sulfuric acid at 20 minutes and mechanical scarification, obtained the best results to break dormancy, with percentages of germination above 80%. Pilon et al (2012) obtained satisfactory results with scaling in sandpaper and sulfuric acid to overcome dormancy in Tachigali vulgaris seeds, with germination percentages of 84% and 71%, respectively.…”
Section: Resultssupporting
confidence: 87%
“…showed the highest values (Table 2). Pereira et al (2015) observed close results with seeds of Tachigali myrmecophila, where the scarification in sandpaper provided a higher average length of the aerial part and the main root, with efficient results for the chemical scarification of 10 and 20 minutes as well. According to Nascimento et al (2009), sandpaper scarification triggered larger average lengths of the main root and shoot seedlings of Parkia platycephala.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation